Frost - Baer, Marianna (New York : Balzer + Bray, 2011)
When Leena Thomas gets her wish to live in an old Victorian house with her two closest friends during their senior year at boarding school, the unexpected arrival of another roommate--a confrontational and eccentric classmate--seems to bring up old anxieties and fears for Leena that may or may not be in her own mind.
Young Adult.
Young Adult
Keywords: Boarding schools -- Juvenile fiction; Dwellings -- Juvenile fiction; Emotional problems of teenagers -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Schools -- Juvenile fiction; Supernatural -- Juvenile fiction; Boarding schools -- Fiction; Dwellings -- Fiction; Emotional problems -- Fiction; Interpersonal relations -- Fiction; Schools -- Fiction; Supernatural -- Fiction; Emotional problems -- Fiction; Houses -- Fiction; Interpersonal relations -- Fiction; Private schools -- Fiction; School stories; Supernatural -- Fiction